1997
DOI: 10.1159/000227661
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Anti-Fas Antibody and Chemotherapeutic Drugs in Ovarian Cancer Cells in vitro

Abstract: To clarify the significance of the Fas antigen (Ag) in gynecologic tumors, its expression in gynecologic cancer cell lines was examined. The Fas Ag was expressed in 6 of 15 cell lines. Five of 8 ovarian cancer cell lines but none of 4 choriocarcinoma cell lines expressed the Fas Ag. In drug-resistant cell lines derived from one of the Fas-positive cells, its expression was not lost after development of resistance to cisplatin, SN-38 or etoposide, but its expression was absent in the cell line resistant to Adri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Human Fas antigen consists of 325 amino acids and transduces death signal conferred by anti-Fas antibody or Fas L. Fas expression was reported in various kinds of human malignancies, including ovarian serous cystadenocarcinoma (OwenSchaub et al, 1994;Hellquist et al, 1997;Wakahara et al, 1997). In our study, 74% of patients with ovarian neoplasms showed Fas expression without significant difference in the frequency of Fas expression between histologic types.…”
Section: Discussionmentioning
confidence: 42%
“…Human Fas antigen consists of 325 amino acids and transduces death signal conferred by anti-Fas antibody or Fas L. Fas expression was reported in various kinds of human malignancies, including ovarian serous cystadenocarcinoma (OwenSchaub et al, 1994;Hellquist et al, 1997;Wakahara et al, 1997). In our study, 74% of patients with ovarian neoplasms showed Fas expression without significant difference in the frequency of Fas expression between histologic types.…”
Section: Discussionmentioning
confidence: 42%
“…Similar results have been reported for FAS-mediated apoptosis in ovarian cell lines. 33,34 In contrast to TRAIL-mediated apoptosis, FAS-mediated apoptosis in ovarian cancer cells was not enhanced by 4HPR pretreatment (Figure 1d). …”
Section: Hpr Enhances Trail-mediated Toxicity In Ovarian Cancer Cellsmentioning
confidence: 92%
“…Fas is activated by binding of Fas ligand, leading to activation of downstream death executioner factors, such as caspase-3, eventually resulting in cell death (Krammer 1999). Fas-induced apoptosis is also believed to be one of the mechanisms involved in cisplatin cytotoxity in OSE cancer cells (Uslu et al 1996, Wakahara et al 1997, a therapy often used as treatment for OSE cancer. We have examined the effect of LH on the occurrence of Fas-induced apoptosis in the human ovarian epithelial cancer cell lines HEY and Caov-3 and determined whether signaling occurs via protein kinase A (PKA) and/or protein kinase C (PKC) activation.…”
Section: Introductionmentioning
confidence: 99%